Structural survey and diagnosis of historical constructions - the experience of the Construction Institute - Esmeralda Paupério (2016)
The sustainable rehabilitation of an historical construction can only be achieved if there is adequate knowledge about its state of conservation. To obtain such knowledge, reliable structural survey and diagnosis procedures need to be employed. An overall definition of the more important technical procedures that need to be considered is addressed to provide general guidelines for the structural survey and diagnosis of historical constructions. A more detailed description of some of the methods is then also performed. Several case studies are then presented to illustrate these approaches, emphasizing the importance of the technical inspection and survey data in the rehabilitation actions that were developed in each case study.